In vivo antioxidant and hepatoprotective effects of methanolic extract of dioclea reflexa seed in rats following acute or chronic liver injury - Iliemene, Uju Dorothy; Atawodi, Sunday Ene-Ojo (Bangladesh Journal of Pharmacology, 2014)
Methanolic extract of Dioclea reflexa seed was investigated following acute or chronic carbon tetrachloride intoxication in male albino rats. In the acute experiment, rats were pre-treated with extract at 5 mg/kg for three days before administration of carbon tetrachloride(0.6 mL/kg) while in the chronic model, rats received extract at 2.5 mg/kg for 12 consecutive days with 72 hourly administration of carbon tetrachloride at 0.3 mL/kg. In both models, the levels of transaminases and malondialdehyde were significantly (p<0.05) reduced in D. reflexa extract treated rats compared to the carbon tetrachloride control, with concomitant boosting in the levels of superoxide dismutase and catalase activities. These results indicate that the seed extract of D. reflexa possess strong antioxidant and hepatoprotective properties in both acute and chronic hepatocellular damage and oxidative stress that it could impact positively on the health of the eastern Nigerian populace that consumes it regularly.